Exploring mufti’s perceptions toward waqf and zakat integration in Malaysia / Siti Nadiah Mohd Ali … [et al.] - Mohd Ali, Siti Nadiah; Mokhtar, Salbiah; Mohd Noor, Abd Halim; Arshad, Huraizah (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
There is a growing number of waqf and zakat project development for asnaf in Malaysia. Although the zakat fund used in several State Islamic Religious Councils (SIRC) comes out with a few projects for asnaf, there is a dearth of empirical studies on the Mufti’s perceptions of waqf zakat integration. The purpose of this paper is to investigate the Mufti’s perceptions toward waqf and zakat integration in project development. The data were collected from Muftis of Peninsular Malaysia through a purposive sampling technique. In total, 11 interviews were conducted. The Mufti’s perceptions were explored on waqf and zakat integration for project development. The qualitative data were analysed for thematic analysis by adopting NVivo’s version 12 steps for data analysis. It was found out that the majority of the Mufti have positive perceptions regarding the waqf and zakat integration as far as integrity is concerned. The themes which emerged from these interviews were integrity, the importance of waqf and zakat integration, fatwa and asnaf welfare issues. This study will guide the waqf and zakat institutions about integrating waqf and zakat projects development for asnaf benefit. This is probably among the uncommon studies on waqf and zakat integration regarding Mufti’s perceptions towards project development.